Lo familiar y lo femenino en la narrativa de Samanta Schweblin (2021)
The Argentine narrator Samanta Schweblin, member of the Granta and Bogotá 39 Selections, is the author of the novels Kentukis, Fever Dream and the books of short stories Siete casas vacías (Seven empty houses) and Mouthful of Birds. Her narrative, due to its characteristics, can be considered feminine (even feminist), as she creates universes from the perspective of women, in which their world —with all its objects, situations, rolls, experiences— is put in evidence and questioned, even from the writing techniques. This article offers a reading of the family environment built on the narrative of the Argentine author, the books Fever Dream (2014) and Mouthful of Birds (2009), from a female voice that can be considered part of that "new canon" in Latin American literature.